INCLUSIVE EDUCATION IN FRANCE AND IN UZBEKISTAN - Kavilova, Tamara (Журнал иностранных языков и лингвистики, 2021)
This article is devoted to the study of the French experience in inclusive education and its introduction into the education system of the Republic of Uzbekistan. The development of inclusive education has become one of the main directions of the policy of our state, because this form of education is designed to guarantee children with special needs in acquiring their worthy place in society.